Generalized binomial coefficients associated with invariant polynomials of two Hermitian matrices (2005)
In this article we define generalized binomial coefficients associated with invariant polynomials of two Hermitian matrix arguments and study their properties. We also evaluate several integrals involving invariant polynomials of two Hermitian matrices.